Transcriptomes Divergence of Ricotia lunaria Between the Two Micro-Climatic Divergent Slopes at “Evolution Canyon” I, Israel - Qian, Chaoju; Yan, Xia; Yin, Hengxia; Fan, Xingke; Yin, Xiaoyue; Sun, Peipei; Li, Zhijun; Nevo, Eviatar; Ma, Xiao-Fei (Frontiers in Genetics, 2018)
As one of the hotspot regions for sympatric speciation studies, Evolution Canyon (EC) became an ideal place for its high level of microclimatic divergence interslopes. In this study, to highlight the genetic mechanisms of sympatric speciation, phenotypic variation on flowering time and transcriptomic divergence were investigated between two ecotypes of Ricotia lunaria, which inhabit the opposite temperate and tropical slopes of EC I (Lower Nahal Oren, Mount Carmel, Israel) separated by 100 m at the bottom of the slopes. Growth chamber results showed that flowering time of the ecotype from south-facing slope population # 3 (SFS 3) was significantly 3 months ahead of the north-facing slope population # 5 (NFS 5). At the same floral development stage, transcriptome analysis showed that 1,064 unigenes were differentially expressed between the two ecotypes, which enriched in the four main pathways involved in abiotic and/or biotic stresses responses, including flavonoid biosynthesis, α-linolenic acid metabolism, plant–pathogen interaction and linoleic acid metabolism. Furthermore, based on Ka/Ks analysis, nine genes were suggested to be involved in the ecological divergence between the two ecotypes, whose homologs functioned in RNA editing, ABA signaling, photoprotective response, chloroplasts protein-conducting channel, and carbohydrate metabolism in Arabidopsis thaliana. Among them, four genes, namely, SPDS1, FCLY, Tic21 and BGLU25, also showed adaptive divergence between R. lunaria and A. thaliana, suggesting that these genes could play an important role in plant speciation, at least in Brassicaceae. Based on results of both the phenotype of flowering time and comparative transcriptome, we hypothesize that, after long-time local adaptations to their interslope microclimatic environments, the molecular functions of these nine genes could have been diverged between the two ecotypes. They might differentially regulate the expression of the downstream genes and pathways that are involved in the interslope abiotic stresses, which could further diverge the flowering time between the two ecotypes, and finally induce the reproductive isolation establishment by natural selection overruling interslope gene flow, promoting sympatric speciation.